A 3D-printing method of fabrication for metals, ceramics, and multi-materials using a universal self-curable technique for robocasting. Issue 4 (23rd December 2019) - Zhang, Danwei; Jonhson, Win; Herng, Tun Seng; Ang, Yong Quan; Yang, Lin; Tan, Swee Ching; Peng, Erwin; He, Hui; Ding, Jun
Abstract : A universal 3D printing technique for metals, ceramics and multi-materials with complex geometries for resultant dense high-quality structures. Abstract : Ceramics and metals are important materials that modern technologies are constructed from. The capability to produce such materials in a complex geometry with good mechanical properties can revolutionize the way we engineer our devices. Current curing techniques pose challenges such as high energy requirements, limitations of materials with high refractive index, tedious post-processing heat treatment processes, uneven drying shrinkages, and brittleness of green bodies. In this paper, a novel modified self-curable epoxide–amine 3D printing system is proposed to print a wide range of ceramics (metal oxides, nitrides, and carbides) and metals without the need for an external curing source. Through this technique, complex multi-material structures (with metal–ceramic and ceramic–ceramic combinations) can also be realized. Tailoring and matching the sintering temperatures of different materials through sintering additives and dopants, combined with a structural design providing maximum adhesion between interfaces, allow us to successfully obtain superior quality sintered multi-material structures. High-quality ceramic and metallic materials have been achieved ( e.g., zirconia with >98% theoretical density). Also, highly conductive metals and magnetic ceramics were printed and shaped uniquely without the need for a sacrificial support. With the addition of low molecular weight plasticizers and a multi-stage heat treatment process, crack-free and dense high-quality integrated multi-material structures fabricated by 3D printing can thus be a reality in the near future.